Komunikasi, Disiplin Kerja, dan Motivasi terhadap Kepuasan Kerja Karyawan - Michael Steven; Khomeiny Yunior; Tommy Tommy; Vincent Vincent (Journal of Management and Bussines (JOMB), 2022)
This study aims to examine and analyze the influence of communication, discipline, motivation on job satisfaction at PT Alfa Scorpii. This research method is quantitative with the sample used is 147 people. The sampling method is simple random sampling. Methods of data analysis using multiple linear regression. The results showed that the t test on the communication variable with value (5.136> 1.976), discipline (3.742> 1.976) and motivation (6.836> 1.976). The results of the F test show a value of 40.189> 2.67. In conclusion, partially has a positive and significant effect on job satisfaction at PT Alfa Scorpii. Simultaneously, the variables of communication, discipline and motivation show a positive and significant impact on customer satisfaction at PT Alfa Scorpii. Keywords: Discipline, Job Satisfaction, Communication, Motivation